2013
DOI: 10.1002/ange.201305276
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Solution Processing of Mesoporous Metal–Sulfide Semiconductors as Light‐Harvesting Photoanodes

Abstract: Strukturierte Absorber: Mesoporöse Filme aus hoch kristallinem Sb2S3 werden durch das Aufstreichen und Tempern einer Vorläufer‐Paste erhalten. Hierbei kann die Porengröße durch die Wahl der Temperatur gesteuert werden. Eine große Oberfläche ermöglicht wiederum einen effizienten Ladungstransfer zu einem polymeren Lochakzeptor, weshalb solche Filme die Basis neuer organisch‐anorganischer Hybrid‐Photovoltaiksysteme bilden könnten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…Alternatively, the exciton splitting could be inefficient in this system. We are unable to determine which of these explanations is correct, however this observation reiterates the need to find a wider bandgap polymer that does not filter light and hinder the maximum currents possible from these types of devices, as previously reported 10…”
contrasting
confidence: 60%
See 2 more Smart Citations
“…Alternatively, the exciton splitting could be inefficient in this system. We are unable to determine which of these explanations is correct, however this observation reiterates the need to find a wider bandgap polymer that does not filter light and hinder the maximum currents possible from these types of devices, as previously reported 10…”
contrasting
confidence: 60%
“…This method offers two main advantages; better definition of connectivity by ensuring a continuous phase before the addition of a polymer and also the ability to tune the chemical/physical properties of the interface between the two phases. To this end, we have recently demonstrated that metal xanthate precursors can be used to fabricate three‐dimensional mesoporous metal sulfide films 10. Specifically, we demonstrated the fabrication of mesoporous Sb 2 S 3 films where we were able to control the mesoporosity of the films through tuning the annealing temperature and were able to show the dependence of charge generation on the interfacial area along with working photovoltaic devices 10.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The organic/inorganic HSCs, with device configuration of ITO/CdS interface layer /P3HT:PC 61 BM:x wt.% CdS or Sb 2 S 3 /MoO 3 /Ag were fabricated as follows: firstly, cadmium xanthate precursor (Di(ethylxanthato- κ 2 S , S ′)bis(pyridine-κ N )cadmium(II), Cd(S 2 COEt) 2 (C 5 H 4 N) 2 , Et = ethy) and antimony xanthate precursor (Tri(ethylxanthato- κ 2 S , S ′)antimony(III), Sb(S 2 COEt) 3 ) were prepared respectively following the previously published procedure [ 26 , 38 , 39 ]. Secondly, a patterned ITO-coated glass with a sheet resistance of 10~15 Ω square −1 was cleaned in de-ionized water, acetone, and isopropanol in turn.…”
Section: Methods/experimentalmentioning
confidence: 99%